From Refugee Camp to Resilient City: Zaatari Refugee Camp, Jordan - Nada Maani (Footprint)
This project is about how architecture can transform a refugee camp into a child friendly city designed around existing social networks. The vision is to respond to the refugee crisis with long-term resilient solutions rather than reactionary ones.